THE NON-CRIMINALIZATION PRINCIPLE IN ACCORDANCE TO THE NEW BRAZILIAN MIGRATION LAW - Moraes, Ana Luisa Zago de (PANORAMA OF BRAZILIAN LAW, 2018)
In the study of migration, one aspect that deserves special attention is the tendency of immigrant’s criminalization by host countries and the mechanisms of international and domestic law to suppress such phenomenon. Hence, the purpose of this article is precisely to address these mechanisms and develop the theoretical construction of the “non- criminalization principle”.